A randomized controlled evaluation of a secondary school mindfulness program for early adolescents: Do we have the recipe right yet?. (December 2017) - Johnson, Catherine; Burke, Christine; Brinkman, Sally; Wade, Tracey
Abstract: Objective: Mindfulness is being promoted in schools as a prevention program despite a current small evidence base. The aim of this research was to conduct a rigorous evaluation of the .b ("Dot be") mindfulness curriculum, with or without parental involvement, compared to a control condition. Method: In a randomized controlled design, students ( M age 13.44, SD 0.33; 45.4% female) across a broad range of socioeconomic indicators received the nine lesson curriculum delivered by an external facilitator with ( N  = 191) or without ( N  = 186) parental involvement, or were allocated to a usual curriculum control group ( N  = 178). Self-report outcome measures were anxiety, depression, weight/shape concerns, wellbeing and mindfulness. Results: There were no differences in outcomes between any of the three groups at post-intervention, six or twelve month follow-up. Between-group effect sizes (Cohen's d ) across the variables ranged from 0.002 to 0.37. A wide range of moderators were examined but none impacted outcome. Conclusions: Further research is required to identify the optimal age, content and length of mindfulness programs for adolescents in universal prevention settings. Trial registration: ACTRN12615001052527. Highlights: We investigated the .b mindfulness program for a second time in early adolescents. We tightened adherence to the manualised curriculum. Parental involvement was added in one arm of the RCT design. We found no differences between the mindfulness groups with/without parental involvement and the control group. Further research is required to identify optimal age and content of school-based mindfulness programs.